Geotechnology applied in precision livestock farming | Geotecnologia aplicada na pecuária de precisão - Alan Cézar Bezerra (Revista Geama, 2016)
The current state of animal production has faced several challenges, such as environmental, animal welfare and food safety. This has generated a new paradigm for the management and animal production. This article aims to review literature regarding livestock precision farming concepts, traceability and its history, traceability in Brazil, traceability of components, identification systems, geotechnology used in precision livestock. We can conclude that geotechnology can assist in herd management, animal performance in optimization of the use of pastures and preservation of natural and minimizing negative impacts resources. Thus, it contributes to the livestock industry can satisfy the food safety requirements, animal welfare and environmental sustainability.